Material-driven fibronectin assembly rescues matrix defects due to mutations in collagen IV in fibroblasts. (September 2020) - Ngandu Mpoyi, Elie; Cantini, Marco; Sin, Yuan Yan; Fleming, Lauren; Zhou, Dennis W.; Costell, Mercedes; Lu, Yinhui; Kadler, Karl; García, Andrés J.; Van Agtmael, Tom; Salmeron-Sanchez, Manuel
Abstract: Basement membranes (BMs) are specialised extracellular matrices that provide structural support to tissues as well as influence cell behaviour and signalling. Mutations in COL4A1/COL4A2, a major BM component, cause a familial form of eye, kidney and cerebrovascular disease, including stroke, while common variants in these genes are a risk factor for intracerebral haemorrhage in the general population. These phenotypes are associated with matrix defects, due to mutant protein incorporation in the BM and/or its absence by endoplasmic reticulum (ER) retention. However, the effects of these mutations on matrix stiffness, the contribution of the matrix to the disease mechanism(s) and its effects on the biology of cells harbouring a collagen IV mutation remain poorly understood. To shed light on this, we employed synthetic polymer biointerfaces, poly(ethyl acrylate) (PEA) and poly(methyl acrylate) (PMA) coated with ECM proteins laminin or fibronectin (FN), to generate controlled microenvironments and investigate their effects on the cellular phenotype of primary fibroblasts harbouring a COL4A2 +/G702D mutation. FN nanonetworks assembled on PEA induced increased deposition and assembly of collagen IV in COL4A2 +/G702D cells, which was associated with reduced ER size and enhanced levels of protein chaperones such as BIP, suggesting increased protein folding capacity of the cell. FN nanonetworks on PEA also partially rescued the reduced stiffness of the deposited matrix and cells, and enhanced cell adhesion through increased actin-myosin contractility, effectively rescuing some of the cellular phenotypes associated with COL4A1/4A2 mutations. The mechanism by which FN nanonetworks enhanced the cell phenotype involved integrin β1 -mediated signalling. Collectively, these results suggest that biomaterials and enhanced integrin signalling via assembled FN are able to shape the matrix and cellular phenotype of the COL4A2 +/G702D mutation in patient-derived cells.